Photocatalytic degradation kinetics in Rhodamine B dye degradation with poriferous TiO2 photocatalyst - Wang, Zheng-Ping; Jiao, Cai-Shan; Chen, Xing-Juan (Journal of marine science and application, 2006)
A type of poriferous TiO2 material was prepared using cetyl trimethyl ammonium bromide as a template agent and butyl tetra titanate as a precursor. Through studying the photocatalytic kinetic activity of Rhodamine B photocatalytic degradation reaction with a UV-1601 PC ultraviolet-visible spectrophotometer, the photocatalytic degradation process of Rhodamine B was found to not correspond to the firstorder kinetic process completely. According to the reaction phenomenon, the photocatalytic degradation process of Rhodamine B with poriferous TiO2 involved two irreversible reactions. The kinetic model was tested using experimental data.